Recent Trends in the Development of Ecological Models Applied on Aquatic Ecosystems - S.E. Jorgensen (The Scientific World Journal)
This paper presents an overview of the application of models on aquatic ecosystems. More than 17% of the models published in the focal journal in the field, Ecological Modelling, are aquatic ecosystem models. An increasing number of papers are dealing with the theoretical aspects of modeling – new modeling approaches and techniques, how models can be used to reveal ecosystem properties, and how models can better reflect the properties of ecosystems. This development implies that today we have more types of models. The characteristics, the advantages, and the disadvantages of these model types are presented briefly. The selection criteria for the presented model types are discussed, and the application of these types to models for aquatic ecosystems is reviewed. A recent improvement in model calibration of particular interest for aquatic ecosystems is presented, and the perspectives resulting from this new calibration procedure and from possible hybrids of the presented model types are discussed.